IMPLEMENTASI HASIL RANCANG BANGUN SISTEM PENDINGIN UNTUK PENGUKURAN TEMPERATUR PEMOTONGAN PADA BENCH DRILL IXION BT 25 - Christian Kariso; Charles Punuhsingon; Rudy Poeng (JURNAL POROS TEKNIK MESIN UNSRAT, 2022)
This research is an experimental study that is testing the drilling process to analyze the decrease in cutting temperature from the implementation of the cooling system design results on the IXION BT 25 bench drill. This test was carried out at the Mechanical Engineering Laboratory of Unsrat. The data used in this study are primary data obtained directly from testing the drilling process without cooling and with cooling by varying the diameter of the drill chisel 8 mm, 12 mm, 17 mm, and 23 mm. The results of this study are in the form of a graph of the relationship between the diameter of the drill bit and the cutting temperature without cooling, the graph of the relationship between the diameter of the drill bit and the cutting temperature with the cooler and the graph of the relationship between the diameter of the drill bit and the cutting temperature without and using a cooler linearly. The conclusion of the research implementation of the cooling system design results for measuring cutting temperature on the bench drill IXION BT 25, shows that in the first experiment for a drill chisel diameter of 8 mm the temperature decreased by 21.7%, in the second experiment for a drill chisel diameter of 12 mm it reduced the temperature to 32. ,5%, in the third experiment for the diameter of the drill chisel 17 mm lower the temperature 65.5% and in the fourth experiment for the diameter of the drill chisel 23 mm lower the temperature 65.2%. Thus, the larger the diameter of the drill chisel used, the greater the temperature drop. Thus the implementation of the results of the cooling system design for measuring the cutting temperature on the IXION BT 25 bench drill can stabilize the cutting temperature so that it will extend the life of the drill tool.Â Keywords: Drill Chisel Diameter, Cutting Temperature, Cooling System Design